Control e identificación de costos y gastos previo al desembolso económico en la empresa constructora Constru-Innova-Ramos - Engracia Calderón, Britany Lidubay (2020)
The present study is directed to the analysis of the control of costs and expenses prior to the economic disbursement made by the construction company Constru-Innova-Ramos Company Accounts In Participation, the same which aimed to demonstrate how efficient this internal process is. In order to understand the categories of conceptual analysis, a descriptive methodology was used by means of which the reality in which the company performs was known, an analysis was made to control costs and expenses; the same ones that allowed establishing the respective conclusions. Among the main findings, it is considered essential to generate measurable and differentiated evaluation criteria between each level of decision-making, in terms of internal control policy and production processes, the flow of costs and expenses are presented in a significant way. for the normal development of the company according to internal policies. Among the conclusions that could be reached is that the company Constru-Innova-Ramos does not have an internal control system that allows it to identify its costs and expenses in a reasonable manner, so it incurs disbursements of money that have not been provided by the administration, reducing accounting reasonableness to its processes.